Studie av omskjutningar i tunneldrivningsprojekt - de Groot, Laura (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2017)
Conventional drill and blast tunnelling consists of mainly seven elements which together makes a cycle. This cycle includes drilling and blasting which are crucial factors in tunnelling projects, as these have a major influence on how the project will progress. After blasting there can be occurrences of under-break with so called bootholes in it and a re-blast is needed. This is expensive and time-consuming, and is therefore indefensible due to causing extra costs as well as a delay in the completion of the whole project. A solution for this problem is needed to avoid blasting second times. Due to laws regulating the allowed fracture zone in tunnel-blasting, contour blasting is performed. The reason behind why bootlegs emerges after blasting is still unknown and depends on many varied factors, such as geology, blast pattern and the volume of explosives used. Different tests are done while blasting, thereafter the results are evaluated and documented. Each test was tried three times to get as a most reliable result as possible. Among others the amount of explosives ranged, double detonators in poor rock sections and a new drill plan was made. The main theory behind this project was that the problem with bootlegs mainly depended om poor geological situations in the rock. None of the test however have been successful enough to solve the problem and after almost every blast there where bootholes in the remaining rock. Recommendations for further testing are using a less amount of explosives as this was a successful method in Björkdalsgruvan in northern Sweden. Another thing worth giving a try is to remove the “helping-row” because it seems like it is breaking the contour-row and not doing any difference.